FILOGENI MOLEKULER BAKTERI DARI MEDIA PEMELIHARAAN ROTIFER YANG DIBERI OLAHAN LIMBAH IKAN SEBAGAI SUMBER NUTRISI - Herlin S Hubu; Stenly Wullur; Veibe Warouw; Elvy L Ginting; Robert A Bara; Adnan S Wantasen (Sam Ratulangi University, 2021)
This study aims to identify and construct molecular phylogeny of an isolate bacteria from culture media of rotifer Brachionus rotudiforis supplied with processed fishery waste feed as nutritional source. The use of fish waste-based food for rotifer showed positive effects on growth and nutrient content of the rotifers. Genomic DNA of the isolate bacteria BRLI- 01 was extracted and the 16S rRNA gene was amplified using primers (8F and 1492F) and further sequenced using Sanger sequence technique. The 16S rRNA gene was analysed using SeqScannerÂ® and MEGAÂ® followed with BLAST (Basic Local Alignment Search Tool) analyses in the NCBI (National Centre for Biotechnology Information). Amplification result of 16S rRNA gene bacteria s NCBI site as a reference for identification and phylogeny of bacterial species. BRLI-01 was successfully cultured on rotifer rearing media. The results of the 16S rRNA gene amplification of the isolate bacteria showed a DNA band with a length of 1400 bp. The BLAST result on the NCBI showed that the isolate bacteria BRLI-01 had a percent identity (98.46%) and is in the same phylogony branching position with Vibrio rotiferianusÂ Keywords: Rotifers, Bacteria, Fish waste, 16S rRNA Genes, Phylogeny identification